A study on relationship between protein-energy malnutrition and other morbidities among under-five children in a rural area of Hooghly district, West Bengal - Tushar Kanti Saha,; Eashin Gazi,; Kallol Bhandari, (Asian Journal of Medical Sciences, 2023)
Background: Malnutrition affects physical growth, morbidity, and mortality of the under-five children. It is an underlying factor in many diseases for children and is particularly prevalent in developing countries, where it affects one out of every three preschool-age children. Aims and Objectives: The aims of this study were to find out the relationship between protein-energy malnutrition and other morbidities among under-five children. Materials and Methods: Community-based prospective longitudinal study was conducted in 1 year duration in a rural area of Hooghly District, West Bengal. By adopting sample size calculation formula 4 pq/L2, total 108 children were participated in the study. With the help of pre-design, pre-tested schedule data were collected by interviewing the care giver, by clinical and anthropometry examination of the children and by record review. Results: Among the study population under-weight, stunted, and wasted were 52%, 37%, and 28%, respectively, whereas malnutrition by all types of classification was 61%. Episode of diarrhea, acute respiratory infections (ARI), and worm infestation were 3.50, 4.12, and 1.38/child/year, respectively. Study shows that rate of total morbidities and prevalence of malnutrition was very much interrelated. Conclusion: Prevalence of malnutrition along with diarrhea, ARI, and worm infestations is common ailments among rural population. Special emphasis should be given for provision of health-care services and promotion and protection of optimal infant feeding practices for the improvement of nutritional as well as health status of the children.